STRESS LEVELS, COPING STRATEGIES, AND PHYSICAL ACTIVITY AMONG CAREGIVERS OF CHILDREN WITH NEUROLOGICAL DISORDERS - Chawla, Renu; Physio, Dimple Choudhry; A, Anjali (MNJ (Malang Neurology Journal), 2026)
Background: Caregivers of children with neurological disorders such as cerebral palsy, epilepsy, ADHD, and Down syndrome often face continuous physical, emotional, and social challenges. These prolonged caregiving responsibilities can increase stress levels, reduce physical activity participation, and affect coping abilities, ultimately impacting caregiver well-being and quality of care provided to the child. Understanding the relationship between stress, coping strategies, and physical activity is important for planning supportive interventions for caregivers. Objective: This study aimed to evaluate stress levels, coping strategies, and physical activity patterns among caregivers of children with neurological disorders and to examine the relationship between these variables. Methods: An observational cross-sectional study was conducted among 100 primary caregivers of children aged 4–17 years diagnosed with neurological disorders. Participants were recruited from the Pediatric OPD of Pt. B. D. Sharma PGIMS, Rohtak, using convenient sampling. Stress levels were assessed using the Depression Anxiety Stress Scale–21 (DASS-21), coping strategies using the Coping Health Inventory for Parents (CHIP), and physical activity using the International Physical Activity Questionnaire (IPAQ-MET). Demographic and clinical variables were recorded and analyzed using SPSS version 25.0 with significance set at p < 0.05. Results: Caregivers demonstrated moderate to high stress levels, with a mean. Coping strategy scores showed considerable variability, while physical activity levels ranged from low to high, with a mean IPAQ-MET score of 2587.98 ± 3399.51. Higher stress levels were significantly associated with lower physical activity participation, whereas effective coping strategies were significantly associated with lower stress levels. Stress, coping strategies, and physical activity were also influenced by the child’s diagnosis, caregiver occupation, and duration of caregiving. Conclusions: Caregivers of children with neurological disorders experience considerable stress closely related to coping abilities and physical activity levels. Interventions promoting adaptive coping strategies and regular physical activity may improve caregiver well-being and support sustainable long-term caregiving.